August Wilson's Fences: The African-American Women's Pursuit Of Dreams Seen From The Perspectives Of Rose Maxson - Kurnia, Nandy lntan (Journal of English and Education (JEE), 2010)
This paper portrays the struggle of people of color to reach their dreams as reflected in August Wilson's "Fences". In his work, he described vividly how African-American men force themselves to be successful in reaching their dreams. However, he did not give a large portion of discussion about women and their dreams. His female characters' dreams are remain unspoken. Moreover there is only one woman, named Rose Maxson, who stands as his female protagonist, while the other female characters are only exist in term of names that are mentioned by the other characters involved in the play. It seems that he only gives chance to Rose to speak up her mind as one of the African-American women. Therefore, she is a source full character that can be used as the media to learn about the way women see the importance of having and reaching their dreams.This paper is based on a library research. The primary data used in the analysis were taken from August Wilson's play, entitled "Fences". The secondary data were collected from articles and historical documents such as autobiographies and notes. Through the use of Liberal Feminist approach and the discussion of the character of Rose (along with her characterization) and the connection between the writer and the history of African-American women, this paper wants to reveal Wilson's point of view on how African- American women see the importance-of having dreams and what they, mostly, do to reach those dreams. Furthermore, the readers will also be able to know what challenges faced by those women in their struggle to gain equal rights and acceptance in the society.Based on the analysis, it can be concluded that Wilson uses Rose, who takes the ideas of reaching dreams as her self-fulfillment into a new direction with less focus on financial gain and put more emphasis on what some people believe as living a simple, fulfilling life, as the agent to open the eyes of (especially) the African American women to think and struggle to reach their dreams, although those dreams are still closely connected to the ideas of fulfilling their roles as the heart of the family.